A Re-examination of the Measurement of Foot Strike Mechanics During Running: The Immediate Effect of Footwear Midsole Thickness - Zhang, Zhenyuan; Lake, Mark (Frontiers in Sports and Active Living, 2022)
Purpose Midsole cushioning thickness (MT) is a key component of running footwear that may influence the stiffness setting of the joints, performance enhancement, and injury prevention. Most studies that have investigated the influence of manipulating shoe midsole characteristics on foot strike patterns and vertical force loading rates have not considered the dynamic conditions of initial landing and the associated initial lower limb joint stiffness. In this study, we examined the effect of running in shoes with large changes in MT on both the posture and dynamics associated with foot strike. Methods 12 injury-free runners with habitual rearfoot strike patterns ran at 4.5 m/s along a 40-m runway in shoe conditions with MT of 30, 42, and 54 mm, respectively. Ground reaction force and the right leg kinematic data were collected. One-way repeated measures ANOVA was conducted to statistically analyze the effect of MT on key variables linked to foot strike. Results Increased midsole thickness resulted in a slightly flatter foot strike posture (p < 0.05), a decreased shank retraction velocity (p < 0.05), and an increase in forward horizontal foot velocity (p < 0.05), all at initial ground contact. Vertical force loading rates were reduced with increasing MT (p < 0.05), but this was associated with large increases in the initial ankle and knee joint stiffness (p < 0.05). Conclusion Adjustments in the initial conditions of contact with the ground during running were seen in both the posture and dynamics of the lower limbs. To help to mitigate the impact severity from foot-ground collision with the thinnest shoe condition, there was an increased shank retraction velocity and decreased forward velocity of the foot at landing. These active impact-moderating adaptations likely served to reduce the changes in impact severity expected due to midsole material properties alone and should be considered in relation to altering the risk of running-related injuries.